The maxillary lateral incisor in the rehabilitation of cleft lip and palate - Tereza,Guida Paola Genovez (2018)
Abstract Objective This study analyzed the maintenance of lateral incisors in the dental rehabilitation of individuals with cleft lip and palate. Material and Methods The study was conducted on a tertiary craniofacial center and comprised retrospective analysis of panoramic and periapical radiographs of Caucasoid individuals with non-syndromic complete unilateral cleft lip and palate, analyzing all radiographs available on the records of each individual, from the first to the last up to 12 years of age. Overall, 2,826 records were reviewed to achieve a sample of 1,000 individuals. Among these, 487 individuals presented the permanent lateral incisors on both cleft and non-cleft sides, which were included in this study. Results The results were evaluated in percentages and by descriptive statistics. The association between maintenance of the lateral incisor and timing of alveolar bone graft were analyzed by the t test. Among the 487 individuals, 265 had not completed treatment, 62 presented insufficient information, and 44 concluded the treatment elsewhere. Among the remaining 116 individuals, the lateral incisor was extracted from 88 (75.86%) of them on the cleft side (CS) and from 23 (19.83%) people on the non-cleft side (NCS). The age at accomplishment of alveolar bone graft was significantly associated with maintenance of the lateral incisor on the cleft side (p<0.01). Most extractions were indicated because of the inadequate positioning on the CS and for midline correction on the NCS. Rehabilitation was primarily completed by orthodontic movement (53 individuals on the CS and 13 individuals on the NCS). Conclusion In conclusion, the lateral incisor on the cleft side was not maintained in most individuals. Positive relationship was observed between extraction of the lateral incisor and age at accomplishment of the alveolar bone graft, suggesting the need to anticipate the initial radiographic evaluation to enhance its maintenance and reduce the procedures required for rehabilitation.